Removal of Ni(II) and Zn(II) from Aqueous Solutions Using Chitosan - Soheil Sobhanardakani (Archives of Hygiene Sciences, 2016)
Background & Aims of the Study:  The increasing levels of toxic heavy metals discharged into the environment have received considerable attention due to the adverse effects on receiving waters. Therefore, the developed adsorbent was assessed for its practical role in removal of metal ions from industrial wastewater. The purpose of the present work is to investigate the removal of Ni(II) and Zn(II) ions by chitosan as an abundant and inexpensive adsorbent.